2004
DOI: 10.1111/j.0014-3820.2004.tb01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Developmental Environment on Signal-Preference Coupling in a Hawaiian Cricket

Abstract: Previous work has suggested that developmental temperature influences expression of the adult male calling song of the cricket, a sexually selected mate recognition signal. The role of developmental temperature in shaping female preference functions, and thus its influence on signal‐preference coupling has not been investigated. In this study, the effects of developmental temperature are examined in both males and females of the Hawaiian cricket, Laupala cerasina, to determine the degree of signal‐preference m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Clinal variation usually indicates that some environmental factors such as temperature, precipitation, or season length vary with latitude or longitude, and these factors, in turn, influence expression of calling songs in crickets. Recent findings that the expression of both male calling songs and female mate preferences depends on developmental temperature (Olvido & Moussear, 1995; Walker, 2000; Grace & Shaw, 2004) suggest the possibility of clinal effects on calling songs in our studies. Divergence in calling song characters may thus arise during development from different temperature regimes between areas of allopatry and sympatry.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Clinal variation usually indicates that some environmental factors such as temperature, precipitation, or season length vary with latitude or longitude, and these factors, in turn, influence expression of calling songs in crickets. Recent findings that the expression of both male calling songs and female mate preferences depends on developmental temperature (Olvido & Moussear, 1995; Walker, 2000; Grace & Shaw, 2004) suggest the possibility of clinal effects on calling songs in our studies. Divergence in calling song characters may thus arise during development from different temperature regimes between areas of allopatry and sympatry.…”
Section: Discussionsupporting
confidence: 47%
“…When recorded at standard temperatures, males reared in high temperature regimes produced calling songs with higher chirp rates (CRs) and carrier frequencies in Allonemobius fasciatus (Olvido & Mousseau, 1995) and with higher pulse rates (PRs) in Gryllus rubens (Walker, 2000) than males reared in low temperature regimes. Grace & Shaw (2004) found that changes in male calling songs and female preference functions induced by developmental temperatures were matched in a Hawaiian cricket Laupala cerasina . That is, female crickets reared in warmer conditions preferred songs with faster PRs produced by males reared in warmer conditions.…”
Section: Introductionmentioning
confidence: 95%
“…Acoustic communication in crickets shows widespread (i) behavioral coupling, where male and female traits are matched within species; (ii) temperature coupling, where cooler males produce slower songs that are preferred by cooler females (5); and (iii) developmental coupling where males reared at cool temperatures sing slower songs that are preferred by females reared at equally cooler temperatures (30)(31)(32). Several authors have hypothesized mechanisms for both the physiological and genetic bases of behavioral coupling (3,5,6,33).…”
Section: Discussionmentioning
confidence: 99%
“…A single degree of freedom in a repeated-measures ANOVA appears insufficient to detect relatively subtle adult phenotypic variation caused by variation in juvenile environment. It is also possible that any effect of juvenile environment may have “decayed” over the adult lifespan of the test subjects (Grace and Shaw 2004). Future studies should consider including more than two experimental levels of juvenile environment and a more precise accounting for adult age.…”
Section: Discussionmentioning
confidence: 99%
“…since Brooks (1882) and Dolbear (1897), only recently have researchers begun to explore how environmental variation during the juvenile stages of the life cycle might shape reproductive behavioral reaction norms, e.g. degree to which male mating call varies systematically with ambient temperature (Whitesell and Walker 1978; Olvido and Mousseau 1995; Grace and Shaw 2004). …”
Section: Introductionmentioning
confidence: 99%